Enhancing Student Active Learning in Strategy and Marketing Analysis Class Using 5E Learning Cycle - Sulaiman, Yaty; Abdul Rahman, Maria; Nik Mat, Nik Kamariah (Universiti Utara Malaysia, 2020)
5E learning cycle was suggested as a better option for students’ learning and has brought a positive impact on students learning education, particularly with theory and practice components. These method of learning is a student’s centre oriented learning model which solely prioritize on students own experiences, creates active participation and built creative critical thinking skills. 5E learning cycle consist of engagement, exploration, explanation, elaboration, and evaluation. This study is intended to determine students’ perceptions of 5E learning cycles in their learning activity and to explore the impact of 5E learning cycles towards student’s active learning. The discussion is based on the information gauged from 42 undergraduate students who enrolled in BPMM3043 Strategy and Marketing Analysis class in Universiti Utara Malaysia. Data will was collected qualitatively from various sources such as students’ reflections, lecturer’s reflections, peer feedback, lecturer’s feedback, and focus group interview. Meanwhile for quantitative method, a survey was developed through Google form. The data was analysed using transcribe technique and regression analysis.